Taking Empowerment to the Next Level: A Multiple-Level Model of Empowerment, Performance, and Satisfaction - Seibert, Scott E.; Silver, Seth R.; Randolph, W. Alan (Academy of Management Journal, 2004)
Most research to date has approached employee empowerment as an individual-level phenomenon. In this study we proposed a work-unit-level construct, empowerment climate, and tested a multiple-level model integrating macro and micro approaches to empowerment. Empowerment climate was shown to be empirically distinct from psychological empowerment and positively related to manager ratings of work-unit performance. A cross-level mediation analysis using hierarchical linear modeling showed that psychological empowerment mediated the relationships between empowerment climate and individual performance and job satisfaction.